Effectiveness on the Environment Based on Government Regulation Number 26 of 2023 concerning Management of Sedimentation Results in the Sea - Riyadi, Panji; Fakrulloh, Zudan Arief (Cognitionis Civitatis et Politicae, 2025)
Marine sedimentation exploitation, regulated in Government Regulation No. 26 of 2023, aims to manage marine sedimentation results, including using sea sand for various economic interests. However, although this regulation aims to maintain the balance of the aquatic ecosystem, its implementation actually poses significant risks to the sustainability of coastal ecosystems, including the potential for small islands to sink. This study examines the impacts of marine sand exploitation on the environment, coastal communities, and the economic sector and evaluates the effectiveness of supervision and administrative sanctions in the regulation. The results of the study indicate that although this regulation includes various obligations for business actors, weak supervision and the lack of effective mitigation measures have the potential to worsen ecological, social, and economic impacts. Therefore, this study recommends a revision of the regulation that pays more attention to ecosystem sustainability and the involvement of coastal communities in decision-making related to marine resource management.